Determinants of Willingness to Communicate among Secondary EFL Learners: A Case Study Approach - Marshalina, Afifah; Suryati, Nunung; Zen, Evynurul Laily (Journal of Language and Literature Studies, 2025)
A key component of language learning is increasing learners’ willingness to communicate (WTC), which is the main objective of second language (L2) instruction. In this study, students’ perceptions of the aspects affecting their desire to communicate in an EFL (English as a Foreign Language) classroom were investigated. Four secondary students participated in semi-structured interviews to collect data for a qualitative case study. They were chosen due to their varied backgrounds in English: two students had prior learning experience and received rich exposure to English, and the other two did not. The selection of students was based on the need to obtain more detailed data. Data were examined with thematic analysis. The results of this study indicated that students exposed to English earlier are more willing to communicate. It clarifies the significant impact of early exposure to English has on students’ preparedness for a more challenging learning environment. Additionally, personal factors like motivation, linguistic aspects, classroom environment, and task design contributed to students’ willingness to communicate in English classrooms. Recognizing these factors is crucial since they influence students’ involvement and communicative practice, both of which are vital to language learning. Lastly, these findings suggest the importance of fostering supportive classroom environments and tailoring instructional strategies to diverse learner needs, offering valuable insights for EFL educators.